Search for the Higgs boson in the H→WW→ℓνjj decay channel at √s=7 TeV with the ATLAS detector - Castro, Nuno Filipe (2012)
A search for the Standard Model Higgs boson has been performed in the H -> WW -> lvjj channel using 4.7 fb(-1) of pp collision data recorded at a centre-of-mass energy of root s = 7 TeV with the ATLAS detector at the Large Hadron Collider. Higgs boson candidates produced in association with zero, one or two jets are included in the analysis to maximize the acceptance for both gluon fusion and weak boson fusion Higgs boson production processes. No significant excess of events is observed over the expected background and limits on the Higgs boson production cross section are derived for a Higgs boson mass in the range 300 GeV < m(H) < 600 GeV. The best sensitivity is reached for m(H) = 400 GeV, where the observed (expected) 95% confidence level upper bound on the cross section for H -> WW produced in association with zero or one jet is 2.2 pb (1.9 pb), corresponding to 1.9 (1.6) times the Standard Model prediction. In the Higgs boson plus two jets channel, which is more sensitive to the weak boson fusion process, the observed (expected) 95% confidence level upper bound on the cross section for H -> WW production with m(H) = 400 GeV is 0.7 pb (0.6 pb), corresponding to 7.9 (6.5) times the Standard Model prediction.